Minor malformations : neonatal or anthropological story? - Šumanović-Glamuzina, Darinka; Božić, Tomica; Brkić, Vesna, liječnica; Robović, Adisa; Saraga-Karačić, Violeta (2009)
Summary: Minor malformations (mM) are mild physical deformities that with their incidence, number and evolution may be external indicators of hidden, more serious disorders. Most often these are recognized by the neonatologists. First studies done some forty years ago showed an average incidence of 15% in the general population of newborns and about 50% in children with major malformations (MM). A study done in Maternity Hospital Mostar covering a one-year cohort of the newborns and assessing 38 mM showed an average incidence 23.7% mM in children without MM. Twelve mM have had a frequency above 1%, many of them in the head region. The most frequent specific mM was a deep sacral dimple (4.6%). Eighteen mM malformations that appeared more often were re-evaluated three months later. A large part (50–80%) disappeared, but a small number (about 17%) were newly discovered. In the newborns with MM, the incidence of mM was 57.5%. 15 of 23 children with MM (65.2%) had more than three associated mM. The highest percentage was in the group of hypotrophic newborns. The connection of mM with MM and specificity of incidence of mM in one population are the reason why the search for mM in the neonatal period could be benefit also for children and whole population
Bibliografija: 25 jed
Keywords: Mala malformacija -- Pilonidalni sinus -- Novorođenčad